2019
DOI: 10.1186/s12967-019-2016-y
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of risk factors for diabetic nephropathy progression and the construction of a prognostic database for chronic kidney diseases

Abstract: Background Diabetic nephropathy (DN) affects about 40% of diabetes mellitus (DM) patients and is the leading cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD) all over the world, especially in high- and middle-income countries. Most DN has been present for years before it is diagnosed. Currently, the treatment of DN is mainly to prevent or delay disease progression. Although many important molecules have been discovered in hypothesis-driven research over the past two decades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 61 publications
(51 reference statements)
0
47
1
2
Order By: Relevance
“…This has been seen in earlier studies as well and re-emphasizes the importance of optimum glycemic control for preventing microvascular complications. 9,10 This study showed that common co-morbidities associated with DN were CAD, hypertension, dyslipidemia and obesity. This finding is similar to that seen in other studies.…”
Section: Patients With Dn Patients Without Dnmentioning
confidence: 92%
“…This has been seen in earlier studies as well and re-emphasizes the importance of optimum glycemic control for preventing microvascular complications. 9,10 This study showed that common co-morbidities associated with DN were CAD, hypertension, dyslipidemia and obesity. This finding is similar to that seen in other studies.…”
Section: Patients With Dn Patients Without Dnmentioning
confidence: 92%
“…The specific pathogenesis is still not fully clear. The incidence of DN accounts for 20%-40% of all diabetic patients, and it is also one of the main causes of death [4]. DN is characterized by edema, hyperglycemia, hypertension, and albuminuria.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is the most common cause of end-stage renal disease (ESRD) worldwide [108]. Pathologic changes in the diabetic kidney including thickening of the glomerular basement membrane, mesangial expansion, proteinuria, inflammation, and fibrosis.…”
Section: Diabetic Nephropathymentioning
confidence: 99%